Gestational age specific anthropometric postnatal percentile charts for neonates born at tertiary hospital in Eastern Nepal - Anjum Shakya; Nisha Keshary Bhatta; Rupa Rajbhandari Singh; Shankar Prasad Yadav; Jitendra Thakur (BMC, 2022)
Abstract Background and objectives Birth weight, Head circumference (HC), and Length are important clinical indicators for evaluation of prenatal growth and identification of neonates requiring detail assessment and monitoring. Gestational age-specific percentile charts are essential tool for both obstetricians and pediatricians in their day to day practice. This study aimed to develop gestational age specific percentile chart of Birth weight, Length and HC for neonates. Methods In this Cross sectional observational study, HC, Birth weight and Length of live singleton neonates from 28 to 42 weeks of gestation fulfilling the inclusion criteria were measured over a period of one year. Mean, standard deviation, and percentiles values for different gestational age were calculated. Graphs were constructed using two way graph and Lowess smoothening method. Results Of total 2662 neonates, male: female ratio was 1.3:1 with maximum neonates in 40 weeks of gestation. The mean Birth weight, HC and Length was 2852.02 gm, 33.6 and 48.42 cm respectively. Overall males have more mean weight than females by 46.35gms. However, mean HC of male and female were similar 33.6 and 33.61 cm respectively and on average males were 0.27 cm longer compared to female. The mean Birth weight, HC and Length at 40 weeks was 3123.43gm (± 427.82), 34.249 cm (± 0.87) and 49.61 cm(± 1.85) respectively. The 10th, 50th and 90th percentile at 40 weeks for Birth weight being 2550gm, 3100gm and 3750gm respectively. The gestational age specific percentile chart and growth curve are appropriately placed in the manuscript. Conclusions The percentile charts in this study may be used as reference for local population and similar data from various parts of the nation can provide a national reference curve for healthy neonates.